KARAKTERISASI SEMI KOKAS DAN ANALISA BILANGAN IODIN PADA PEMBUATAN KARBON AKTIF TANAH GAMBUT MENGGUNAKAN AKTIVASI H2 0 - Handri Anjoko; Rahmi Dewi; Usman Malik (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A  research  has been  conducted  to   analyze  characteristics  of  semi-coke  and  the best activated carbon  absorption  after  the activation process  by  determining the  iodine number and refering to  the  Indonesian National Standard  of  activated carbon  materials. The  carbonization  temperatures of peat  soil  were  400oC,  500oC,  and  600°C.  Activated process was carried out at  temperature of 900 °C with  duration time  20, 40  and 60 minutes. Result of the  research  showed that the  best sample of semi-coke  was the sample which was carbonized at  600oC  and  with its duration  time of  60  minutes.  The sample characteristics of the moisture content, ash content, volatile matter content,  fixed carbon content  and heat value,  respectively were 4.91%, 12.24%, 13.43%, 69.42% and 4085.22  Kal/g.  The highest  iodine  number of the best sample was  686  mg/g  and yield was 38% at  600oC  carbonization temperature  and duration time of  60  minutes  with  theactivation temperature of 900oC and duration time of 60 minutes.